The work simulation of flow rate for carriages' repair as a multiphase, multiplex and multidisciplinary system of mass service - Myamlin, V. V.; Myamlin, S. V. (Science and Transport Progress, 2011)
The algorithm of computer simulation of the flexible flow for repair of cars as a multiphase polychannel manyobject queuing system is presented. The basic operators of the model are given and their work is described.